Development of Page Flip-Based Electronic Teaching Materials for IPAS Learning in Fifth-Grade Elementary School - Lisa Andary; Syahrial Syahrial; Destrinelli Destrinelli (Universitas Negeri Semarang, 2025)
Background - Innovation in teaching materials is crucial in 21st-century learning, especially to address the limitations of conventional methods in engaging students and improving comprehension in Science and Social Studies (IPAS). Page Flip-based electronic teaching materials offer an interactive alternative aligned with the Merdeka Curriculum's emphasis on technology integration. Purpose - This study aims to develop and evaluate the validity, practicality, and effectiveness of Page Flip-based electronic teaching materials for fifth-grade elementary IPAS learning. Method/approach - This research employed a Research and Development (R&D) method using the ADDIE model for over one semester. The study involved 28 fifth-grade students and one teacher from SD Negeri 043/IV Kota Jambi. Data was collected through expert validation, small-group trials, and field trials across several learning sessions. The development used 3D Page Flip Professional software, and assessments were conducted through questionnaires, observations, and pretest-post test scores. Findings - Expert validation by content, media, and language experts showed a high level of validity (final scores above 4.50 on a 5-point scale). Trials revealed a 23% improvement in students' understanding in small groups and a 26% improvement during field trials. Students responded positively to the multimedia and interactive features, while teachers rated the materials as very effective and easy to use. However, implementation faced challenges such as limited digital infrastructure (many schools lack sufficient devices) and teachers' unfamiliarity with educational technology. Conclusions - Page Flip-based teaching materials are empirically proven to be effective, practical, and valid for enhancing students' conceptual understanding, motivation, and digital skills in IPAS. With proper support and training, these materials can become a transformative tool in primary education. Novelty/Originality/Value - This study contributes uniquely by integrating Page Flip technology within the Merdeka Curriculum framework and evaluating not only the overall effectiveness but also usability and contextual barriers, making it a reference for future development of interactive learning media.